2022
DOI: 10.3390/cancers14184359
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell-Free DNA in Renal Cell Carcinoma: The New Era of Precision Medicine

Abstract: Tumor biopsy is still the gold standard for diagnosing and prognosis renal cell carcinoma (RCC). However, its invasiveness, costs, and inability to accurately picture tumor heterogeneity represent major limitations to this procedure. Analysis of circulating cell-free DNA (cfDNA) is a non-invasive cost-effective technique that has the potential to ease cancer detection and prognosis. In particular, a growing body of evidence suggests that cfDNA could be a complementary tool to identify and prognosticate RCC whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…Two patients had a complete response, while two patients had a partial response with elevated levels prior to treatment. Seven patients experienced progressive disease and showed variability in pre-and post-treatment cfDNA levels [179]. Similar outcomes are found in patients treated with ICI.…”
Section: Monitoring Therapeutic Response In Renal Cancer Treatmentsupporting
confidence: 71%
“…Two patients had a complete response, while two patients had a partial response with elevated levels prior to treatment. Seven patients experienced progressive disease and showed variability in pre-and post-treatment cfDNA levels [179]. Similar outcomes are found in patients treated with ICI.…”
Section: Monitoring Therapeutic Response In Renal Cancer Treatmentsupporting
confidence: 71%
“…Numerous studies have suggested the diagnostic value of methylation markers in RCC [27]. However, to date there are very limited data on the prognostic role of liquid biopsy in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, kinetic evaluation and molecular profiling through BEAMing (beads, emulsions, amplification, and magnetics), next-generation sequencing (NGS), and digital droplet PCR (ddPCR) are potential non-invasive cancer management modalities. Recently, a surge in cfDNA-based identification of pathological signatures, staging, and development of analytical methods for cancer theranostics with clinical translations has been observed [226,227]. Hence, the significance of cfDNA in cancer diagnosis and precision medicine is underscored by its potential and routine use in the clinical diagnosis and management of several cancers.…”
Section: Theranostic Insights In Tumor-tme-bioenergtics Interfacementioning
confidence: 99%